The Biopolitics of Manning the Royal Navy in Late Stuart England. (14th July 2017) - Neufeld, Matthew
Abstract: This article examines the Royal Navy's implementation between 1690 and 1710 of new and publicly controversial policies, grounded in quantitative technologies, to manage the multitude of English seamen. These policies and their promotion can be profitably interpreted using the Foucauldian concept of biopolitics. Naval biopolitics meant mobilizing and promoting political arithmetic in the service of the fiscal-naval state. Thus, naval biopolitics was both a new model of statecraft and a form of state publicity, that is, a genre of works that strove to influence government policy and public opinion by promoting projects that a polemicist argued the state could and should undertake to better govern its subjects. The directives, legislation, and pamphlet literature of naval biopolitics projected a fiscal-naval state capable of counting, tracking, and mobilizing the national stock of seamen onto its ships in a predictable, salubrious, and, most crucially, orderly fashion. However, English naval biopolitics endured much longer as a genre of state propaganda than as a method of mobilizing the population of seamen onto ships.